A Novel Android Application Design Based on Fuzzy Ontologies to Carry Out Local Based Group Decision Making Processes - Morente-Molinera, Juan Antonio; Wikstroem, R.; Carlsson, Christer; Cabrerizo, Francisco Javier; Perez, I. J.; Herrera-Viedma, Enrique (Modeling decisions for artificial intelligence (MDAI 2016), 2020)
The appearance of Web 2.0 and mobile technologies, the increase of users participating on the Internet and the high amount of available information have created the necessity of designing tools capable of making the most out of this environment. In this paper, the design of an Android application that is capable of aiding some experts in carrying out a group decision making process in Web 2.0 and mobile environments is presented. For this purpose, Fuzzy Ontologies are used in order to deal with the high amount of information available for the users. Thanks to the way that they deal with the information, they are used in order to retrieve a small set of alternatives that the users can utilize in order to carry out group decision making processes with a feasible set of valid alternatives.
Keywords: group decision making; fuzzy ontologies; decision support system; WOS(2); Scopus(2)